(untitled) (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2026)
The stiffness of a two-dimensional portal frame is governed by the interaction among geometry, section properties, joint rigidity, support restraints, and loading pattern. This paper revises and expands an initial SAP2000 analysis of a 2D portal frame by incorporating a unit audit, model-data reconstruction, normalized sensitivity formulations, a verification procedure, and a mechanically consistent interpretation of the results. The baseline model represents a one-story, one-bay rigid portal made of ASTM A992 steel and subjected to vertical and horizontal distributed loads under linear static analysis. The original outputs show maximum raw values of 7086.87 for shear force, 20673.05 for bending moment, -5874.94 for compressive axial force, and 0.2022 for lateral displacement. Because the screenshots do not explicitly preserve the active output units, these values are treated as raw software results; under an N-m unit system, the force values correspond to 7.087 kN and 5.875 kN, while the moment corresponds to 20.673 kN·m. The normalized screening analysis demonstrates that the flexural response is highly sensitive to column height and beam span because displacement scales approximately with the cube of member length. A 10% increase in height is expected to increase lateral displacement by about 33.1%, whereas a 20% increase produces an increase of about 72.8% when flexural action dominates. A 20% reduction in the second moment of area increases deformation by approximately 25%. Support conditions also modify moment redistribution and drift, with fixed-fixed bases providing the highest restraint compared with configurations involving rotational releases. The revised study emphasizes that SAP2000 results should not be used for design decisions before the model units, geometry, reactions, rotations, and section properties have been independently verified.